Polypyrrole as a Nanofiller: Comparative Effects on the Properties of Polycaprolactone Scaffolds for Potential Myocardial Tissue Applications - Ana M. Muñoz-Gonzalez; Dianney Clavijo-Grimaldo (Chemical Engineering Transactions)
This study investigates the incorporation of polypyrrole (PPy) as a nanofiller in polycaprolactone (PCL) electrospun nanofiber scaffolds for potential application in cardiac tissue engineering (CTE). Characterization techniques including SEM, FTIR, tensile strength testing, and contact angle measurements were employed. PPy incorporation enhances scaffold uniformity and reduces average diameter compared to pure PCL scaffolds, which is beneficial for tissue formation, mechanical behavior, and facilitating charge transport critical for electrical conductivity in CTE. FTIR spectra confirm successful PPy incorporation, and mechanical testing demonstrates increased strain capacity, peak stress, and Young's Modulus in PCL+PPy scaffolds. Contact angle measurements indicate water adhesion to PCL+PPy scaffolds, beneficial for cell bioactivity in tissue engineering applications. This research serves as a preliminary step towards the development of a scaffold that could be effectively used in tissue engineering, particularly in CTE, as it combines the biocompatibility of PCL with a conductive polymer in a nanofibrous format.